论新加坡 “组屋” 的翻译功能及其社会属性的演变 = An analysis on the evolving functionalism and social qualities of “Zu Wu” in translation - 陈敏华 Chen Minhua (2019)
在新加坡多元文化的社会语境中，翻译活动与各种社会因素之间相互影响、相互渗透，从而促进各族的文化与语言交流。翻译活动在特定的社会语境中能发挥一定程度的社会功能并且对社会发展具有强大的推动作用与影响力。同时，一个社会在经济、政治和文化上的发展也会对翻译活动施加压力与影响，使其在观念、内容和形式上受到制约。因此，两者在交流与碰撞之中相互依赖、相互制约。 “组屋”是新加坡特有的华文译词，与社会成员的生活息息相关，在新加坡公共住屋的历史发展过程中扮演著重要角色。该译词随著新加坡国家转型、公共住屋政策的改变在不同时期发挥不同的价值与功能。同时，新加坡社会在发展过程中赋予该译词特定的社会属性和意识形态，这一现象与新加坡社会的政治、文化及社会因素密切相关。 In Singapore’s multicultural context, translation activities and social factors are interrelated and interpenetrated, promoting multicultural and multilingual interactions. With the rise of Socio-translation studies, translation is able to perform specific functions in a particular social context and influence the development of the society to a substantial extent. Relatively, a society’s development in the economic, political and cultural aspect can cause pressure and influence on translation activities, causing it to be restrained in terms of concepts, contents and styles. Therefore, both factors can either complement or restrict each other during interaction. “Zu Wu” is a unique representative of Chinese vocabulary within Singapore’s social context. Although it has close ties with members of the society, there is limited level of sensitivity and understanding for this term. The term “ZuWu” has played an important role in Singapore’s Public Housing History. The evolving social functions of “Zu Wu” reflects specific social phenomenon and values during different developmental stages in Singapore’s society amidst national building and evolving Public Housing Policies. The term “Zu Wu” is also a form of rewriting produced with Singapore’s ideological and political constraints within its social context.